Trend in total terrestrial water storage at the European Russia detected based on GRACE DATA - I. Yu. Savin; M. L. Markov; S. V. Ovechkin; V. A. Isaev (Бюллетень Почвенного института им. В.В. Докучаева, 2016)
The data obtained by GRACE satellite allowed comprehensively analyzing the dynamics of total terrestrial water storage within the period from 2003 to 2012 at the territory of European Russia. Having compared the satellite data and the information on the dynamics of the groundwater level obtained in the course of field survey by using 12 evenly distributed bore holes at the studied territory (Central Federal and North-Caucasian Federal regions), it is worth emphasizing that there is a clearly expressed co-variation between the satellite images and the groundwater depth. The analysis of trend in total water content identified by satellite data showed that it is positive towards the north-western and negative in the south and south-eastern part of European Russia. The total content of terrestrial water storage reveals periodical changes in the range from 3 to 8-9 years. The prolonged periods are observed in central and north-western parts, being shortened towards the north and south-east of the studied territory. The obtained data serve as evidence of periodically changing the total terrestrial water storage but its minimum will be observed in the east of Northern Caucasus, in Vologda, Yaroslavl, Moscow and Kostroma regions in 2016, in central part and Krasnodar region in 2018-2019 and in Kirov and Perm’ regions in 2016-2017. The results of the given studies can find a use in long-term forecasting of crop yields, in soil mapping and cultivation of new fruit plantations.